Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445467
|View full text |Cite
|
Sign up to set email alerts
|

How the Design of YouTube Influences User Sense of Agency

Abstract: In the attention economy, video apps employ design mechanisms like autoplay that exploit psychological vulnerabilities to maximize watch time. Consequently, many people feel a lack of agency over their app use, which is linked to negative life effects such as loss of sleep. Prior design research has innovated external mechanisms that police multiple apps, such as lockout timers. In this work, we shift the focus to how the internal mechanisms of an app can support user agency, taking the popular YouTube mobile … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 77 publications
0
39
0
1
Order By: Relevance
“…A recent study [36] showed how the designs of YouTube's internal mechanisms such as auto-play, recommendations, and advertisements support a sense of agency. It discovered that autoplay and recommendations impair sense of agency while search and playlists support it.…”
Section: Understanding Smartphone Use Behaviorsmentioning
confidence: 99%
“…A recent study [36] showed how the designs of YouTube's internal mechanisms such as auto-play, recommendations, and advertisements support a sense of agency. It discovered that autoplay and recommendations impair sense of agency while search and playlists support it.…”
Section: Understanding Smartphone Use Behaviorsmentioning
confidence: 99%
“…Also, the principal usability of extension systems has already been widely demonstrated on the web and in research studies leveraging browser extensions. We plan to conduct user studies for specific use cases of app extensions, for example to increase satisfaction in Facebook or YouTube use, in future research, similar to previous research on the web [45,47].…”
Section: Discussionmentioning
confidence: 99%
“…The harms arising from the current design of the app ecosystem are multi-faceted, growing and widespread. They can include the loss of privacy [11,71], dark patterns [32,51,57], digital distraction [26,[45][46][47], digital inclusion [56,67], discrimination and algorithmic fairness [7,10] and harmful social media content [36]. Addressing these harms is particularly relevant in a world that is recovering from the COVID-19 pandemic, and is spending more time on their mobile devices than ever before [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model also relates to questions about how design choices can influence user behavior and welfare, often studied in the HCI community. Examples include the impacts of design on agency [16], persuasive technology [7], dark patterns [10], and behavioral change [24,18,19]. Our hope is that our model can provide some insight into what types of design interventions might help users, when they would be appropriate, and how to measure their impacts.…”
Section: Related Workmentioning
confidence: 99%